Digital Rhetoric Integration Gaps In Learning Business Persuasive Writing - Nurfidah Nurfidah; Vismaia S. Damaianti; Dadang S. Anshori; Khaerudin Kurniawan (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The transformation of digital business communication has shifted persuasive practices from linear textual approaches toward multimodal, interactive, and data-driven communication. However, business persuasive writing instruction in higher education remains largely conventional, limiting the development of multimodal competence, audience analysis, and data utilization. This study aims to identify the gap in the integration of digital rhetoric in business persuasive writing instruction at Lombok Business Academy (AKBIL). This study employed a mixed-methods approach with a sequential explanatory design, involving a survey of 80 students, analysis of written documents, and interviews with students and lecturers. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis to enrich interpretation. The findings indicate that the overall level of digital rhetoric integration is moderate (M = 3.12). Audience awareness shows a relatively higher score (M = 3.34), yet remains general and not supported by data-driven analytics. Multimodal integration (M = 3.05) is not yet strategic, as visual elements are primarily used decoratively. Data-driven persuasion emerges as the weakest dimension (M = 2.84), characterized by limited use of quantitative evidence and data visualization. Qualitative findings further reveal that instruction remains text-oriented, with limited pedagogical readiness among lecturers and low levels of student data literacy. The study highlights a gap between the demands of digital business communication and current pedagogical practices. Therefore, it underscores the need for developing a digital–rhetorical pedagogy model that systematically integrates multiliteracies, data-driven audience analysis, and evidence-based argumentation in business persuasive writing instruction.